Międzyorganizacyjne relacje W procesach zarządzania: formy – marketing – zachowania strategiczne : зб. пр. - Kot, J.; Lypchuk, V. et. al. (Politechnika Świętokrzyska, 2019)
Contemporary acceleration of globalisation and competition leads organization to apply different than in the 20th century behaviours in relations to other entities operating on the market. Adaptation of modern enterprises to previously unknown complex and turbulent environment imposes the need for continuous and immediate adjustability of relevant management methods. It is a precondition for implementation of strategic objectives and appropriate management methods to achieve competitive advantages. Networking and cooperation became internal strategic goal of contemporary enterprises. Many authors appreciate the phenomenon of cooperation between economic units acting within the chain without taking into consideration simultaneously ongoing process of competition between them.
Keywords: управління; маркетинг в управлінні